Factors Influencing the Adoption of Productivity Enhancement Practices in Pepper Cultivation in Sri Lanka - Salma, S.F.; Umashankar, K. (Sabaragamuwa University of SriLanka, 2022)
1. Introduction Sri Lanka is popularly known as the “Spice Island” and acquainted with the “Spice Route” from East to West for many centuries. Pepper is known as “King of the Spices” since it is widely used and extensively demanded spice around the globe. Pepper is generally attributed to as “Black gold” due to its luxurious nature and used as commodity money (Ministry of Minor Export Crop Promotion, 2014). Sri Lanka ranks fifth concerning the pepper cultivated extent and seventh in production, with a world market share of around 5% (SLEDB, 2019). The Sri Lankan Export Development Board (SLEDB) statistics show that the country exported nearly Rs.11.5 billion worth of pepper in 2018, estimated as Rs.12.7 billion in 2017. Pepper fetches a sizable foreign exchange to Sri Lanka annually. Nevertheless, it has been reported that pepper productivity in Sri Lanka is comparatively low. Compared to the average export by Sri Lanka during the last decade, pepper export declined by 31% in 2019 (IPC, 2020). Nevertheless, Sri Lanka plays a crucial role in the world market under the ‘Ceylon Spice’ trade name due to its inherent superior quality. Taking this advantage to negotiate the intense competition in the world market, improving the productivity of the pepper will undoubtedly open up the way for Sri Lanka to explore high-end markets in USA and EU while enhancing the per capita income of the pepper farmers. However, it seems that the application in the field is not following the recommendations. In order to explore the problems in the field, the effort needed to accelerate the adoption of the productivity enhancement practices, it is necessary to carry out a study by observing farmers’ cultivation directly in the field and interviewing them. This study aims to explore the factors influencing the adoption of productivity enhancement practices by pepper farmers in Sri Lanka.